DROUGHT TOLERANCE OF SOME SOYBEAN VARIETIES IN NEWLY LAND - & et al., Khattab (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Soybean is the most important pulse crop in the world and especially Egypt. It’s import a lot of soybean.  Water is one of the major limiting factors of soybean production in semiarid regions as Egypt. Therefore, choosing the appropriate irrigation system and quantity are very important for obtaining high crop production and overcoming the lack of water and not affect yield. Experiments ware conducted carried out during summer season at years 2017 and 2018, in privet Farm in north Delta, in Qalbsho area, Belqas Center, Dakahlia Government, Egypt, to investigate production of five varieties of soybean (Giza 22, Giza 21, Crawford, Giza 111 and Giza 35), affected by three irrigation intervals (4 and 6 days) and treatment (potassium k 2%, proline 3%, and K + proline) were arranged in split split plot design with three replications in sandy soil under drip irrigation system. Results showed that the drip irrigation lead to increase of all growth yield characters all varieties. Variety of Crawford had a significant effect on plant height; number of pods/plant, hundred seed weight, and seed yield compare other treatments. The variety Giza 21 had low readings compare with other varieties.